Tinjauan Yuridis Terhadap Tindak Pidana dalam Kasus Kekerasan dalam Rumah Tangga (Studi Kasus: Putusan No 1119/Pid.Sus/2024/PN Mdn) - Yesi Enjelina Br Karo; Suhaila Zulkifli; Tajuddin Noor (CV WAHANA PUBLIKASI, 2026)
The increasing incidence of domestic violence in Indonesia and the inadequate safeguards in place to protect victims, especially women, prompted this study. The psychological and physiological effects of domestic abuse necessitate an all-encompassing strategy for addressing this human rights violation. Case No. 1119/Pid.Sus/2024/PN Medan and the factors that the court took into account when making a decision are the subjects of this research. Utilising a statutory framework and case study methodology, this research employs a normative legal approach. It employs descriptive analysis of primary, secondary, and tertiary legal sources. Based on the rules laid out by Law No. 23 of 2004 on the Elimination of Domestic Violence, the components of the crime of physical violence within the home have been satisfied, according to the results of the study. A medical examination report confirms that the victim has received medical assistance as a measure of protection. In terms of psychological healing and rehabilitation, however, victim protection has fallen short of expectations. There are both legal and non-legal factors that the judge took into account when making the decision. While legitimate evidence is the judge's reliance in a legal proceeding, consideration of mitigating factors, such as the defendant's age and confession, is considered in a non-legal proceeding. In comparison to the maximum penalty, the eight-month prison term was thought to be quite light. Finally, victims of domestic violence still do not have complete legal protection; this calls for stricter implementation of laws that help victims heal and discourage abuse.